Chapter Os príncipes e as princesas de Florbela - da Silva, Fabio Mario (Libere carte, 2023)
Images of "princes" and "princesses" can be found in a number of Florbela Espanca's works. Indeed in some poems she goes as far as to represent herself as such, highlighting these terms in both titles and content, notably, in two sonnets. Our intention here is to analyze these representations first as something recurrent in European literature and then by examining the way Florbela takes them up, deploying two very characteristic angles of her poetics, namely her values. However, we will first review the historical context in which the poetess lived, more specifically in Vila Viçosa, with its palaces and castles,which housed the last of Portugal's kings.